Ecosystem services : global issues, local practices - Jacobs, Sander; Dendoncker, Nicolas; Keune, Hans. (San Diego, CA : Elsevier, 2014)
Ecosystem Services: Global Issues, Local Practices is a hands-on, transdisciplinary reflection on ecosystem services directed toward the future development of research, practice, and implementation by professionals. The diversity of values assigned to ecosystems and their services are used to inform policy from local to global scales.'--Publisher description.
Inclusive ecosystem services valuation -- Ecosystem services and their monetary value -- Biodiversity and ecosystem services -- Ecosystem service indicators: are we measuring what we want to manage? -- Inquiring into the governance of ecosystem services: an introduction -- Monetary valuation of ecosystem services: unresolvable problems with the standard economic model -- Biodiversity and ecosystem services: opposed visions, opposed paradigms -- Earth system services - a global science perspective on ecosystem services -- Ecosystem services in a societal context -- The value of the ecosystem services concept in economic and biodiversity policy -- Valuation of ES: challenges and policy use -- Ecosystem services in Belgian environmental policy-making: expectations and challenges linked to the conceptualization and valuation of ecosystem services -- Ecosystem services governance: managing complexity? -- Ecosystem service assessments: science or pragmatism? -- Negotiated complexity in ecosystem services science and policymaking -- The natural relation between biodiversity and public health: an ecosystem services perspective -- Global trade impacts on biodiversity and ecosystem services -- CICES going local: ecosystem services classification adapted for a highly populated country -- The ecosystem services valuation tool and its future developments -- EBI - an index for delivery of ecosystem service bundles -- ES thinking and some of its implications: a critical note from a rural development perspective -- Enhancing ecosystem services in Belgian agriculture through agroecology: a vision for a farming with a future -- Ecosystem service practices -- Reflections from policy practice -- (How) can financial institutions contribute to sustainable use of ecosystem services? -- Making natural capital and ecosystem services operational in Europe through biodiversity offsetting and habitat banking -- SKB, Snowman, and ecosystem services -- Contribution of DG environment of federal public service health, food chain safety and environment -- Relevance of an ecosystem services approach in southern Belgium -- A participatory approach to wildlife management in Walloon farmlands -- Ecosystem services for Wallonia -- Relevance of the concept of ecosystem services in the practice of Brussels environment (BE)-- Contribution of the Agency for Nature and Forests -- Integrating ecosystem services in rural development projects in Flanders -- Reflection on the relevance and use of ecosystem services to the LNE department -- Obstacles to use an ecosystem services concept in agriculture -- The concept of ecosystems services -- Ecosystem services in Natuurpunt -- Ecosystem services in nature education in the province of West Flanders -- Integrating the concept of ecosystem services in the province of Antwerp: the inland dunes project -- Bosland: application of the ecosystem services concept in a new style of forest management.
Includes bibliographical references and index.
Keywords: Ecosystem services